Pengaruh Model Discovery Learning Terhadap Self-Efficacy Pada Hasil Belajar Afektif Mata Pelajaran IPA Siswa Kelas V di SD Islam Assalam Bandar Lampung - Insani Lintang Mahesa; Nur Asiah; Harjoni Desky; Hasan Sastra Negara (Departement of Mathematics Education, 2024)
The choice of learning model greatly influences student learning outcomes in class. This research aims to determine the differences between students who learn using the Discovery Learning model and students who learn using problem-based learning. This research is a type of quantitative research. The population of this study was fifth-grade students at Assalam Islamic Elementary School, Bandar Lampung. The total sample of 52 students consisting of two classes was taken using a purposive sampling technique pretest-posttest Non-Equivalent Control Group Design. The research results show that there is a difference in the Discovery Learning model > PBL with tcount > table (6.482 > 2.056). By doing this research, is my small contribution to the knowledge